The mediating effect of employee engagement on the relationship between perceived organizational support (POS) and organizational citizenship behavior (OCB) - Aini Wizana, Ismail (2014)
The main purpose of this study is to identify the mediating effect of employee engagement on the relationship between perceived organizational support and organization citizenship behavior among employees at Alor Setar Prison Department. Data was collected through a questionnaire survey of 200 respondents using the approach of quantitative research methods. Analysis of the quantitative data suggests that there is a relationship between perceived organizational support and organization citizenship behavior. The result suggested that there is a significant and positive positive relationship. Except that, there also have significant relationship between perceived organizational support and employee engagement. The results also shows there have relationship between employee engagement and organization citizenship behavior. And lastly is this research also examines the mediating effect of employee engagement on the relationship between perceived organizational support and organization citizenship. The finding showed that employee engagement full mediate the perceived organizational support and organization citizenship behavior.